Prevalencia de resultado positivo de la citología para vaginosis bacteriana candidiasis y tricomoniasis en una empresa social del estado de Medellín (Colombia), 2010-2012 (2014)
Objective: To determine the prevalence of positive cytology results for bacterial vaginosis, candidiasis and vaginal trichomoniasis, and distribution by age, birth control method and place of residence. Materials and methods: Cross-sectional study of cytology samples from women seen between 2010 and 2012 at Metrosalud, a network of institutions comprising 50 healthcare centres and level I hospitals in Medellín, Colombia. All the female population under the subsidized insurance regime was included, and inadequate samples due to absence of cells, excess red or white blood cells, and defective smear were excluded. A secondary source of information was used. Data were stored and analysed using the SPSS 21®, with summary measurements and absolute and relative frequencies. Results: Overall, 206,035 records were included. The prevalence of bacterial vaginosis was 18 %, and the prevalence of candidiasis and trichomoniasis was 4.7 % and 0.8 %, respectively. The subgroups with the highest prevalence of infections were adolescents with 22.8 % bacterial vaginosis, 9.2 % candidiasis and 1.0 % trichomoniasis. Among women using the intrauterine device (IUD), the prevalence was 25.6 %, 5.1 % and 1.2 %, respectively. Conclusion: A high prevalence of the infections studied was found, mainly among adolescents and IUD users. This information is useful for healthcare decision-making and for evaluating the relevance of structuring screening programs for genitourinary tract infections together with screening for cervical and uterine cancer.